Neonatal Safety of Elective Family-Centered Caesarean Sections: A Cohort Study - Narayen, Ilona C.; Mulder, Estelle E. M.; Boers, Kim E.; van Vonderen, Jeroen J.; Wolters, Vera E. R. A.; Freeman, Liv M.; Te Pas, Arjan B. (Frontiers in Pediatrics, 2018)
BACKGROUND: Although little data are available concerning safety for newborns, family centered caesarean sections (FCS) are increasingly implemented. With FCS mothers can see the delivery of their baby, followed by direct skin-to-skin contact. We evaluated the safety for newborns born with FCS in the Leiden University Medical Center (LUMC), where FCS was implemented in June 2014 for singleton pregnancies with a gestational age (GA) ≥ 38 weeks and without increased risks for respiratory morbidity. METHODS: The incidence of respiratory pathology, unplanned admission, and hypothermia in infants born after FCS in LUMC were retrospectively reviewed and compared with a historical cohort of standard elective caesarean sections (CS). RESULTS: From June 2014 to November 2015 92 FCS were performed, and compared to 71 standard CS in 2013. Incidence of respiratory morbidity, hypothermia, temperatures at arrival at the department, GA, and birth weight were comparable (ns). Unplanned admission occurred more often after FCS when compared to standard CS (21% vs 7%; p=0.03), probably due to SpO2 monitoring. There was no increase in respiratory pathology (8% vs 6%, ns). One third of the babies were separated from their mother during or after FCS. CONCLUSION: Unplanned neonatal admissions after elective CS increased after implementing FCS, without an increase in respiratory morbidity or hypothermia. SpO2 monitoring might have a contribution. Separation from the mother occurred often.